The Concept of Psychospiritual Well-Being From Western and Islamic Perspectives: A Conceptual Discussion - Fathiah Shamsuddin; Siti Nubailah Mohd Yusof; Nurhafizah Mohd. Sukor (Global Academic Excellence (M) Sdn Bhd (GAE), 2026)
Indexed by MyCite